An Analysis of Lexical Presuppositions and Its Triggers Found in Interstellar Movie - Putu Merta Yasa; Nissa Puspitaning Adni (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to explore lexical presuppositions and their triggers found in the film Interstellar. Lexical presuppositions are a type of presupposition that arises due to the presence of certain words or expressions that inherently carry additional meanings, thus giving rise to assumptions that are not explicitly stated but can still be understood by the listener or viewer. Thus, lexical presuppositions play an important role in building implicit meaning and depth of dialogue in audiovisual works. This study uses a descriptive qualitative method to identify and analyze the forms of lexical presuppositions that appear in the film. Data were collected through documentation and note-taking techniques, by carefully transcribing dialogues from the film Interstellar, then classifying them based on the theory of presuppositions proposed by Yule (1996) and Levinson (1983). The results of the study indicate that there are three types of lexical presupposition triggers in the film's dialogue, namely implicative verbs, change-of-state verbs, and interactive verbs. Of the 59 lexical presuppositions found, the change-of-state verb category was the most dominant, with 49 entries, followed by implicative and interactive verbs. These findings indicate that changes of state implied by certain verbs are frequently used in films to implicitly convey background information without having to directly state it. Furthermore, the use of lexical presuppositions has been shown to help create efficient, natural, and subtext-rich dialogue, supporting story development while enriching the audience's experience. By utilizing specific linguistic triggers, the dialogue in Interstellar is able to establish context, establish relationships between characters, and provide in-depth narrative clues. This research is expected to contribute to the study of pragmatics, particularly in understanding the role of lexical presuppositions in film, and to open up opportunities for further research on their application in various genres and languages.